Palladacycle-catalyzed asymmetric hydrophosphination of enones for synthesis of C*- and P*-chiral tertiary phosphines - Pullarkat, Sumod A. (2013)
A highly reactive and stereoselective hydrophosphination of enones catalyzed by palladacycles for the synthesis of C*- and P*-chiral tertiary phosphines has been developed. When Ph2PH was employed as the hydrophosphinating reagent, a series of C*-chiral tertiary phosphines were synthesized (C*–P bond formation) in high yields with excellent enantioselectivities, and a single recrystallization provides access to their enantiomerically pure forms. When racemic secondary phosphines rac-R3(R4)PH were utilized, a series of tertiary phosphines containing both C*- and P*-chiral centers were generated (C*–P* bond formation) in high yields with good diastereo- and enantioselectivities. The stereoelectronic factors involved in the catalytic cycle have been revealed.